2012
DOI: 10.4141/cjss2011-074
|View full text |Cite
|
Sign up to set email alerts
|

Urea fertilizer forms affect grain corn yield and nitrogen use efficiency

Abstract: Controlled-and slow-release nitrogen (N) fertilizers have been commonly used in high-value applications, such as horticultural production. Traditional controlledrelease products have not been economical for use in major grain crops because of high cost and low crop prices. New economical, controlled-release fertilizers are available for use in field crops such as corn (Zea mays L.), wheat (Triticum aestivum L.), and other commodity grains. Technology improvements have reduced manufacturing costs, while high N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 37 publications
9
46
0
9
Order By: Relevance
“…For example, Gagnon et al (2012) reported that grain corn yields were higher with PCU than with untreated urea in Quebec but the agronomic benefits of PCU were less consistent for small grain crops on the Canadian prairies, silage corn (Zea mays L.) in British Columbia, or potatoes (Solanum tuberosum) in New Brunswick (Soon et al 2011;Grant et al 2012;Zebarth et al 2012). Hyatt et al (2010) reported higher potato yields and lower N 2 O emissions from PCU than from conventional urea on sandy soils in Minnesota.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gagnon et al (2012) reported that grain corn yields were higher with PCU than with untreated urea in Quebec but the agronomic benefits of PCU were less consistent for small grain crops on the Canadian prairies, silage corn (Zea mays L.) in British Columbia, or potatoes (Solanum tuberosum) in New Brunswick (Soon et al 2011;Grant et al 2012;Zebarth et al 2012). Hyatt et al (2010) reported higher potato yields and lower N 2 O emissions from PCU than from conventional urea on sandy soils in Minnesota.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information about these EENFs is provided in Motavalli et al (2008) [24]. Many studies have shown that EENFs can improve corn yields and NUE under wet soil conditions [25][26][27]. In-season N deficiencies caused by N losses under waterlogged soil conditions after initial pre-plant N applications may lower plant N uptake and reduce crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…One such product is ESN, which consists of urea with a polymer coating that is permeable to water and gradually releases N over the growing season at a rate dependent on temperature. ESN typically costs only 15Á30% more than uncoated urea and substantially less than earlier versions of a similar product (Gagnon et al 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the past, CRU products have been considered too expensive for widespread use in small grain production, but recent developments have led to a lower-cost polymer-coated urea products that have made the widespread use of these products in small grain and oilseed production more attractive (Gagnon et al 2012;Grant et al 2012). In the US agricultural market, the consumption of polymer-coated fertilizers has risen at an average annual rate of 14% during the 2001Á2009 period, indicating the growing acceptance of these products (Landels 2010).…”
Section: Literature Reviewmentioning
confidence: 99%